2020
DOI: 10.1016/j.nicl.2020.102433
|View full text |Cite
|
Sign up to set email alerts
|

High-resolution metabolic imaging of high-grade gliomas using 7T-CRT-FID-MRSI

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(51 citation statements)
references
References 54 publications
1
48
0
Order By: Relevance
“…The increase in tP i intensity was dominated by the extracellular contribution, which is in line with our earlier observations ( 10 ) (3 of 5 patients with HGG were already presented). In a recently published high-resolution 1 H MRSI study on a larger cohort of patients with HGG ( 31 ), the tCr intensity showed varying trends across tumor subsegments and individual patients, with tCr reductions typically occurring in the necrosis. Our observation of an insignificant change of PCr intensities in tumor tissue across the cohort might correspond to this, despite the clear reduction of the PCr intensity in the central tumor region observed in examples Figures 1F , 3 .…”
Section: Discussionmentioning
confidence: 99%
“…The increase in tP i intensity was dominated by the extracellular contribution, which is in line with our earlier observations ( 10 ) (3 of 5 patients with HGG were already presented). In a recently published high-resolution 1 H MRSI study on a larger cohort of patients with HGG ( 31 ), the tCr intensity showed varying trends across tumor subsegments and individual patients, with tCr reductions typically occurring in the necrosis. Our observation of an insignificant change of PCr intensities in tumor tissue across the cohort might correspond to this, despite the clear reduction of the PCr intensity in the central tumor region observed in examples Figures 1F , 3 .…”
Section: Discussionmentioning
confidence: 99%
“…Magnetic resonance spectroscopy (MRS) at higher field strengths improves SNR and spectral dispersion, leading to improved sensitivity and specificity, respectively, to different chemical species and metabolites. MRS has the potential to improve the detection of metabolites for tumor characterization; however, the technical challenges of increased SAR, magnetic field inhomogeneities, and fast T2*-relaxation can impose constraints on the acquisition of MRS data at 7 T [ 60 62 ]. Despite these limitations, earlier research at 7 T was able to demonstrate the application of a short-echo spin-echo MRS sequence to detect characteristic differences in regions of tumor versus normal appearing brain and successfully discriminate between short-echo metabolites, particularly glutamate and glutamine, although with low spatial resolutio n[ 63 ]; this differentiation remains elusive at field strengths of 3 T and below [ 60 ].…”
Section: Ultrahigh Field Mrimentioning
confidence: 99%
“…MRS has the potential to improve the detection of metabolites for tumor characterization; however, the technical challenges of increased SAR, magnetic field inhomogeneities, and fast T2*-relaxation can impose constraints on the acquisition of MRS data at 7 T [ 60 62 ]. Despite these limitations, earlier research at 7 T was able to demonstrate the application of a short-echo spin-echo MRS sequence to detect characteristic differences in regions of tumor versus normal appearing brain and successfully discriminate between short-echo metabolites, particularly glutamate and glutamine, although with low spatial resolutio n[ 63 ]; this differentiation remains elusive at field strengths of 3 T and below [ 60 ]. The last decade has seen different MRS acquisition approaches to offset some of the challenges at ultrahigh field imaging [ 60 , 64 67 ].…”
Section: Ultrahigh Field Mrimentioning
confidence: 99%
See 2 more Smart Citations